(untitled) (Research, Society and Development, 2024)
Introduction: The advancement of stem cell therapies represents a significant milestone in regenerative medicine, offering new perspectives for the treatment of neurodegenerative diseases. Induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs) emerge as promising options for neuronal regeneration, particularly in conditions such as Parkinson’s disease. However, the transition of these therapies from research to clinical practice faces considerable challenges. Objectives: This article aims to review the current literature on the use of stem cell therapies for treating neurodegenerative diseases, addressing recent advances, types of cells used, mechanisms of action, and ongoing challenges. The review seeks to provide a comprehensive view of the progress and limitations in this field, contributing to the development of more effective therapeutic strategies. Results: The review revealed that both iPSCs and ESCs have the potential to differentiate into various types of neuronal cells, enabling the replacement of damaged neurons. Clinical and preclinical trials indicate improvements in motor and cognitive function, with notable progress in the treatment of Parkinson’s disease. However, the practical application of these therapies faces challenges such as tumor formation, immune rejection, and the need for functional integration of transplanted cells. Mesenchymal stem cells (MSCs) also show promise, particularly due to their lower ethical controversy and ease of procurement. Conclusion: Stem cell therapies have transformative potential for treating neurodegenerative diseases, offering hope for significant improvements in patient quality of life. However, overcoming associated challenges, such as long-term safety and efficacy, is crucial for the successful implementation of these therapies. Continued research and development are essential to fully realize the therapeutic potential of stem cells.